# Use implicit differentiation to find partial z/partial x and partial z/partial y. x^2 + 4y^2 +...

## Question:

Use implicit differentiation to find {eq}\displaystyle \frac{\partial z}{\partial x} \ \ and \ \ \frac{\partial z}{\partial y}\ {/eq}.

{eq}x^2 + 4y^2 + 5z^2 = 7 {/eq}

## Implicit Partial Differentiation:

Most of the problems we do in differentiation are explicit differentiation. Implicit differentiation, on the other hand, allows us to find {eq}\displaystyle \frac{dy}{dx} {/eq} without solving the equation for y.

In the following problem, we use formulae like:

- {eq}\displaystyle \frac{\partial(x^a)}{\partial x} = ax^{a-1} {/eq}

## Answer and Explanation: 1

Become a Study.com member to unlock this answer! Create your account

View this answerGiven:

{eq}\displaystyle x^2 + 4y^2 + 5z^2 = 7 {/eq}

On partial differentiation with respect to x, we get

{eq}\displaystyle \begin{align} \frac...

See full answer below.

#### Ask a question

Our experts can answer your tough homework and study questions.

Ask a question Ask a question#### Search Answers

#### Learn more about this topic:

from

Chapter 6 / Lesson 5Explicit differentiation is used when 'y' is isolated, whereas implicit differentiation can be used similar to the chain rule when 'y' is not isolated. Learn more about implicit differentiation through examples of formulas and graphs.

#### Related to this Question

- Use implicit differentiation to find partial z/partial x and partial z/partial y. yz + x*ln y = z^2.
- Use implicit differentiation to find partial z/partial x and partial z/partial y. x^2 - y^2 + z^2 - 2z = 4.
- Use implicit differentiation to find partial z/partial x and partial z/partial y. x^2 + 2y^2 + 3z^2 = 2.
- Use implicit differentiation to find partial z/partial x and partial z/partial y. e^z = xyz.
- Use implicit differentiation to find {partial z / partial x} and {partial z / partial y}. x^2 + 4 y^2 + 7 z^2 = 9
- Use implicit differentiation to find partial z/partial x and partial z/partial y. x^2 + 2y^2 + 3z^2 = 1.
- Use implicit differentiation to find \frac { \partial z } { \partial x } and \frac { \partial z } { \partial y }. \operatorname { sin } ( x y z ) = x + 3 y + 3 z
- Using implicit differentiation, find partial z/partial x from the formula x^3 + 2y^3 + z^3 - 3xyz - 2y + 3 = 0 .
- Use implicit differentiation to find {partial z}/{partial x} and {partial z}/{partial y}. x^2 + y^2 + z^2 = 3 x y z
- Use implicit differentiation to find {partial z }/{partial x } and {partial z }/{partial y } if x^2 + y^2 - z^2 = 2x(y + z).
- Use implicit differentiation to find \frac { \partial z } { \partial x } and \frac { \partial z } { \partial y } y z = \operatorname { ln } ( x + z )
- Use implicit differentiation to find {partial z}/{partial x} and {partial z}/{partial y}. y z = ln (x + z)
- Use implicit differentiation to find partial z/ partial x and partial z/ partial y. x^2 + 4y^2 + 5z^2 = 2
- Calculate the derivative using implicit differentiation: partial w/partial z, x^4 w + w^9 + wz^2 + 9yz = 0.
- Calculate the derivative using implicit differentiation: partial w/partial z, x^8w + w^4 + wz^2 + 3yz =0.
- Use implicit differentiation to find (partial z)/(partial x). 4x^5 y^2 - 5y^3 + 3yz^2 = 0.
- Use implicit differentiation to find partial z / partial x and partial z / partial y. x^5 + y^4 + z^8 = 8 x y z.
- Use implicit differentiation to find partial z/ partial x and partial z/partial y. x^2 + 2y^2 + 7z^2 = 8
- Use the implicit differentiation to find (partial f)/(partial x), and (partial f)/(partial y), if x y^2 + yz^2 + zx^2 = 0.
- Find the indicated partial derivative. u= x^a y^b z^c partial ^6 u/partial x partial y^2 partial z^3 =
- Use implicit differentiation to find {\partial z}{\partial x} \enspace and \enspace {\partial z}{\partial y} ,if yz + x \ln y = z^2 .
- Find the indicated partial derivative(s). V = ln (r + s^2 + t^3); partial^3 V / partial r partial s partial t
- Use implicit differentiation to find \frac{\partial z}{\partial x} and \frac{\partial z}{ \partial y}. x^2 + 8y^2 + 5z^2 = 2
- Find the indicated partial derivative. z= u square root v - w; partial^3 z / partial u partial v partial w.
- Use implicit differentiation to find partial z partial x and partial z partial y e 2 z = x y z
- Use implicit differentiation to find partial z / partial x and partial z / partial y if ln (x y + y z + x z) = 5, (x greater than 0, y greater than 0, z greater than 0).
- Use implicit differentiation to find fraction {partial w}{partial x} and fraction {partial w}{partial y} for w = Squareroot {(u + v)(x + y)}; u = x - y, v = x + y
- Find the partial derivatives at the point (-2pi, -1, -pi) if w = x^2 + y^2 + z^2 and ysinz + zsinx = 0 . (a) partial w / partial x, (b) partial w / partial z.
- Calculate the derivative using implicit differentiation: partial w/partial z, (x^4)w + w^4 + wz^2 + 3yz = 0. partial w/partial z =
- Find the partial derivatives partial f/partial y, partial f/partial z, if they exist, of the function f(x, y, z) = 3x/(1 + cos^2(x^3 y)) e^(x^2 z).
- Find the following partial derivatives of the function f(x,y,z)= sin (6xy+7yz+3xz). \partial f / \partial x = \partial ^2 f / \partial x \partial y = \partial ^3 f / \partial x \partial y \partial z =
- Use implicit differentiation to find partial z / partial x. 8 x y^2 + 6 y z^2 + 10 z x^2 = 7.
- Calculate the derivative using implicit differentiation: \frac{\partial w }{\partial z} x ^2w + w ^2 +wz^2 +5yz = 0.
- 1. Compute the partial derivatives given: z = x / {x^5 - y^3}. A. partial z / partial x. B. partial z / partial y. 2. Compute the indicated partial derivative. f (x, y) = 3 x e^{-2 x y}. f_{x y}(-2, 2
- Find the first partial derivatives of f (x, y) = 1x - 3y / 1x + 3y at the point (x, y) = (1, 4). (a) partial t / partial x _(1, 4). (b) partial t / partial y_(1, 4).
- Find the first partial derivatives of f (x, y, z) = z arc tan (y x) at the point (3, 3, 5). A. partial f / partial x (3, 3, 5). B. partial f / partial y (3, 3, 5). C. partial f / partial z (3, 3, 5).
- Find the first partial derivatives of f (x, y, z) = z arc tan (yx) at the point (5, 5, -4). (A) partial f / partial x (5, 5, -4). (B) partial f / partial y (5, 5, -4). (C) partial f / partial z (5, 5,
- Find the first partial derivatives of f (x, y) = {x - 3 y} / {x + 3 y} at the point (x, y) = (4, 3). (a) partial f / partial x (4, 3). (b) partial f / partial y (4, 3).
- Use the Chain Rule to find the indicated partial derivatives. u = x4 + yz, x = pr cos(theta), y = pr sin(theta), z = p + r , p = 1, r = 2, theta = 0 Find partial u/partial p , partial u/partial r , p
- Use the Chain Rule to find the indicated partial derivatives. z = x^4 + x^2y, x = s + 2t - u, y = stu^2 when s = 2, t = 4, u = 5. Find: partial z / partial s , partial z / partial t , partial z / part
- Use the Chain Rule to find the indicated partial derivatives. z = x^3 + xy^4, x = uv^4 + w^3, y = u + ve^w. Find [{partial z} / {partial u}], [{partial z} / {partial v}], [{partial z} / {partial w}],
- Use the Chain Rule to find the indicated partial derivatives. z = x^4 + x^2 y, x = s + 2 t - u, y = s t u^{22}; find partial z / partial s, partial z / partial t, partial z / partial u when s = 5, t =
- Find the indicated partial derivative. u = e^{3r\Theta } sin (\Theta ). \frac{\partial^3u }{\partial r^2\partial\Theta }
- Evaluate the indicated partial derivatives. z = \sin (5x^3y + 7xy^2);\\ \partial z / \partial x , \partial z / \partial y
- Use the chain rule to find partial z/partial s and partial z/partial t. z=tan (u/v), u=6s+5t, v=5s-6t.
- Use the Chain Rule to find {partial z/partial s} and {partial z/partial t}. z = tan (u/v), u = 4 s + 7 t, v = 7 s - 4 t
- Use the chain rule to find partial f / partial u, and partial f / partial v, if f(x, y) = cos(xy), x(u, v) = u + v and y(u, v) = u - v.
- Use the Chain Rule to find partial z / partial s and partial z / partial t. z = (x - y)^7, x = (s^2)t, y = s(t^2).
- Use the Chain Rule to find the indicated partial derivatives. R = ln (u^2 + v^2 + w^2), u = x + 8y, v = 4x - y, w = 2xy; Compute partial R / partial x , partial R / partial y, when x = y = 4.
- Let x y z + \frac { 1 } { x y z } = z ^ { 2 }. Use implicit partial differentiation to find \frac { \partial z } { \partial x } and \frac { \partial z } { \partial y }.
- Find the first partial derivatives of the function. f (x, y) = x^7 y^9 + 7 x^5 y. (a) partial f / partial x. (b) partial f / partial y.
- Given 5xy^3 - 3x^2z + 2xyz = 0, use implicit differentiation to find \frac {\partial z}{\partial x} and \frac {\partial z}{\partial y}.
- Calculate the partial derivative. \frac {\partial z}{\partial x} and \frac {\partial z}{\partial y} for z = x^6e^{7y}
- Let z = {1} / {x^2 y}. Calculate the partial derivative {partial^2 z} / {partial x partial y}.
- Use the chain rule to find partial z / partial s and partial z / partial t, where z=x^2+xy+y^2, x=3s + 4t, y=5s + 6t.
- Use the Chain Rule to find the indicated partial derivatives. N = (p + q) / (p + r), p = u + vw, q = v + uw, r = w + uv; partial N / partial u, partial N / partial v, partial N / partial w when u = 7,
- Use the Chain Rule to find the indicated partial derivatives. R = ln (u^2 + v^2 + w^2), u = x + 3 y, v = 8 x - y, w = 2 x y; partial R / partial x , partial R / partial y when x = y = 1.
- Find the first partial derivatives (partial z / partial x and partial z / partial y) of the function, z = (9x + 8y)^6.
- Using the implicit differentiation to find \displaystyle \frac{\partial z}{\partial x} and \displaystyle \frac{\partial z }{\partial y }. e^{\large{6z=xyz
- Use the Chain Rule to find the indicated partial derivatives. z = x^4 + x^2 y, x = s + 2t - u, y = stu^2; partial z/partial s, partial z/partial t, partial z/partial u when s = 3, t = 2, u = 1.
- Use the Chain Rule to find the indicated partial derivatives. z = x^4 + x^2 y, x = s + 2t - u, y = stu^2; partial z/partial s, partial z/partial t, partial z/partial u when s = 3, t = 5, u = 2.
- Use the Chain Rule to find the indicated partial derivatives. z = x^2 + x y^3, x = u v^3 + w^2, y = u + v e^w {partial z / partial u}, {partial z / partial v}, {partial z / partial w} when u = 2, v
- Assume the equation \frac{1}{w^{2}+x^{2+\frac{1}{w^{2}+y^{2=1 defines w as a function of x and y. Use implicit differentiation to find \partial w / \partial y at (x, y. w) = (1, 1, 1).
- Find the partial derivatives partial z / partial s and partial z / partial t. Justify your answer. z (x, y) = (e^x) (sin (y)), if x = s (t^2) and y = (s^2) t .
- Find the following derivatives. z_s and z_t, where z = e^{9x + 8y}, x = 4st and y = 5s + 5t a. {partial z / partial x} (Express using x and y as the variables.) b. {partial x / partial s} (Express usi
- Find the indicated partial derivatives. f(x,y) = x^3 - 3xy^2 + 6y; frac{partial^2f}{partial x^2}, frac{partial^2f}{partial y^2}, frac{partial^2f}{partial y partial x}
- Find the indicated partial derivatives. z = xye^(xy) - 2x^3 y^3; (partial z)/(partial y); (partial^2 z)/(partial y^2).
- Find the partial derivative. Find fraction partial f partial x 1, - 5 when f x, y = 2x + 5y^2 a. 14 b. - 92 c. - 46 d. 8
- Calculate the derivative, partial w / partial z, using implicit differentiation: x^5 w + w^9 + w z^2 + 7 y z = 0.
- Use the Chain Rule to find the indicated partial derivatives. z = x^3 + xy^2, x = uv^2 + w^3, y = u + ve^w (partial z)/(partial u), (partial z)/(partial v), (partial z)/(partial w)when u = 2, v = 1, w
- Use the Chain Rule to find the indicated partial derivatives. z = x^4 + x^2y; x = s + 2t - u; y = stu^2 \partial z/\partial s, \partial z / \partial t, \partial z/\partial u when s = 5, t = 4 and u = 1.
- Use the Chain Rule to find the indicated partial derivatives. R = ln (u^2 + v^2 + w^2), u = x + 9 y, v = 5 x - y, w = 2 x y; partial R / partial x, partial R / partial y when x = y = 1
- Use the Chain Rule to find the indicated partial derivatives. R = ln (u^2 + v^2 + w^2) ; u = x + 8 y, v = 7 x - y, w = 3 x y ; {partial R / partial x}, {partial R / partial y} when x = y = 1. {partia
- Find the indicated partial derivative. W = square root {u + v^2}; {partial^3 W} / {partial u^2 partial v}
- Find the partial derivative when w=4x^2+4y^2+z^2, x= rho sin phi cos theta, y=rho sin phi sin theta, z= rho cos phi. Find partial w/partial rho, partial v/partial phi, and partial w/partial theta.
- 1) Find partial w partial v when u = - 1 , v = 2 i f w = x y + I n z , x = v 2 u , y = u + v , z = c o s u 2) Find the derivative of function at p
- Use Chain Rule to find expression for partial z / partial u and partial z / partial w, if z = f (x, y), x = (u, w), g = (w, t).
- Find the partial derivatives \frac{\partial^w }{\partial x}, \frac{\partial^w }{\partial y} and \frac{\partial^w }{\partial z} for the function: w = 4x ^2 + 7 yz ^2.
- Find the indicated partial derivative. z = u \sqrt{v - w}; \frac{\partial^3 z}{\partial u \partial v \partial w}
- Use the Chain Rule to find the indicated partial derivatives. u = sqrt(r^2+s^2), r = y + x cos(t), s = x + y sin(t);(partial u)/(partial x), (partial u)/(partial y), (partial u)/(partial t) when x = 1
- Let f(x,y, z) = x^3yz + y^2z^5. Find the partial derivative fraction {partial^3}{partial x partial z partial y} f(x,y, z)
- Find the first partial derivatives of f(x,y) = (2x - y)/(2x + y) at the point (x,y) = (4,4) partial f partial x(4,4) partial f partial y(4,4)
- Use the Chain Rule to find the indicated partial derivatives. M= xe^(y- z^3), x = 8uv, y = u - v, z = u + v; find (partial M)/(partial u), (partial M)/(partial v) when u = 2, v = -2
- Find the first partial derivatives of the function. w = ln (x + 2 y + 5 z) {partial w / partial x} = {partial w / partial y} = {partial w / partial z} =
- Find the first partial derivatives of the function. w = ln (x + 9 y + 5 z). (a) partial w / partial x. (b) partial w / partial y. (c) partial w / partial z.
- Use the following equation to find\frac {\partial z}{\partial x}and\frac {\partial z}{\partial y}\frac {\partial z}{\partial x}-\frac {\frac {\partial F}{\partial x\frac {\partial F}{\partial x}
- Find the partial (or mixed partial) derivative. Given f(x,y) = \frac{4x^2}{y} + \frac{y^2}{2x} find f_{xy} (x,y).
- Using implicit differentiation, find (\partial z/ \partial x) and (\partial z/ \partial y), given that y^{2} - 2xz^{2} + xyz - 3 = 0
- Use the Chain Rule to evaluate the partial derivative at the point specified. partial g / partial s at s = 2, where g(x, y) = x^2 - y^2, x = s^2 + 3, y = 3 - 2 s. partial g / partial s|_{s=2} =
- Use the Chain Rule to evaluate the partial derivative at the point specified. partial f / partial u and partial f / partial v at (u, v) = (-1, 1), where f (x, y, z) = x^3 + y z^2, x = u^2 + v, y = u + v^2, z = u v.
- Calculate the derivative using implicit differentiation: partial w partial z, x^4w+w^7+wz^2+8yz=0
- Calculate the derivative using implicit differentiation: {partial w} / {partial z}, x^4 w + w^2 + w z^2 + 3 y z = 0
- Find both first partial derivatives. z = 12 y^2 square root x (a) {partial z} / {partial x} (b) {partial z} / {partial y}
- Calculate the derivatives using implicit differentiation: Partial differentiation U/ Partial differentiation V and and Partial differentiation T/Partial differentiation U of
- (a) Use chain rule to find the partial derivatives {partial z} / {partial u} and {partial z} / {partial v} of z = e^{x^2 y}, where x(u, v) = square root {u v} and y (u, v) = 1 / v. (b) Express {partial z} / {partial u} and {partial z} / {partial v} only i
- Use implicit differentiation to find the first partial derivatives. z = e^x sin(y + z).
- Use the Chain Rule to find the indicated partial derivatives. z = x^3 + xy^2, x = uv^2 + w^3, y = u + v*e^w (partial z)/(partial u), (partial z)/(partial v), (partial z)/(partial w) when u = 2, v = 1, w = 0
- Find \frac{ \partial w }{ \partial s } and \frac{ \partial w }{ \partial t } by using the appropriate Chain Rule. w = xyz, x = s + 7t, y = s - 7t, z = st^2
- Given z=e^{2u}v^3, x =u^3+v^3, y=uv-v^2. Use the chain rule and implicit differentiation to obtain (partial z/partial y) when u=1 and v=1.
- Use implicit differentiation to find the partial derivatives z_x and z_y for the function z(x, y) defined by the relation yz^2 + xz = e^{xyz}.